Caça às bruxas: a criminalização do aborto e as implicações para as mulheres na atualidade - ZAHLUTH, Carolina Messeder (Universidade Federal da Bahia, 2023)
The article aims to discuss the similarities between the current debate on the criminalization of abortion and the historical witch hunt in the Late Middle Ages and in Modernity Age, seeking to punctuate the effects that this relationship causes on women's bodies and experiences. For this, is made a brief contextualization of the history of the witch-hunt as an essential event for the diffusion of capitalism and expropriation of the bodies and reproductive functions of women, as well as to contextualize the current abortion debate in Brazil as a tension between the feminist movements and the conversational and religious groups. Three main similarities have been identified between witch hunts and the current criminalization of abortion: domination and expropriation of women's bodies and reproductive functions; the two periods persecute, kill and make black, poor and peripheral women vulnerable; and both create and perpetuate a misogynist culture that incites violence and hate crimes against women.